LANGUAGE STYLE USED BY ARMY WIVES AT SUPPORT COMPANY OF MECHANIZED INFANTRY 643 IN ANJONGAN DISTRICT PONTIANAK - Amrina Sari, Riski (Jurnal Ilmiah Spectral, 2019)
This research explains the language style that is used by army wives at support company of mechanized infantry 643 in Anjongan District Pontianak. The purposes of this research are to identify kinds of language style that is used by army wives at Support Company of mechanized infantry 643. The method of this study is descriptive qualitative research. The participants of this research are 23 army wives at Support Company of mechanized infantry 643 in Anjongan District Pontianak. The data was taken through observing the daily conversation among army wives, reading and selecting the utterances from army wives’ group. The researcher found the following results, that there are three k inds of language style that used by army wives at Support Company of mechanized infantry 643 in Anjungan District. They are Formal style, Consultative style and Casual style. In this research, the researcher hopes that the result will be useful for further researchers who are interested to conduct the similar study. It is hoped that this research can give more information and contribution for sociolinguistic field of study especially in the types of language style.